Modeling hot carrier damage interaction between on and off modes for 28 nm AC RF applications. (November 2021) - Garba-Seybou, T.; Bravaix, A.; Federspiel, X.; Cacho, F.
Abstract: Improving device aging models requires to consider hot-carrier degradation (HCD) between On/Off modes and interaction of these different damage rate mechanisms as well as the dynamic effects. As DC characterization of HCD modes might be insufficient, it is rather necessary to check the quasi-static validity when we seek to model the degradation under realistic dynamic stress by a succession of static states. We present a detailed analysis of the interactions of HCD under On and Off state in N-FETs devices using a compact modeling based on an empirical model. Pulsed stressing by measure-stress-measure method is further used to analyze the switching time dependence of HCD and Off modes for an accurate AC RF aging modeling. This reliability methodology is useful to close the gap between the simple models used for DC HCD characterization and the degradation involved in power amplifiers under AC RF signals.